Racial Evolution of an Urban Planet: Scenes From the North American Frontier - Wyly, Elvin (Frontiers in Sustainable Cities, 2022)
In the Summer of 2020, as the latest coronavirus quickened its evolutionary journeys through the human mobilities of planetary urban systems, the research journal of the U.S. Department of Housing and Urban Development published an article by the world's most famous urban economist. Edward Glaeser's article, “The Closing of America's Urban Frontier,” celebrates the influential interpretation of U.S. history offered by Frederick Jackson Turner in a lecture delivered in Chicago in 1893, as part of Glaeser's advocacy of neoliberal, supply-side deregulated city-building as social policy. Yet Glaeser carefully evades the fundamental ethnoracial inequalities at the heart of Turner's frontier thesis, which were inseparable from the Social Darwinist hijacking of evolutionary thought that corrupted economics and other social sciences beginning in the late 19th century. In this paper, the Glaeser-Turner genealogy is used to interpret today's evolving materialities and discourses of race, class, identity, and urbanism. A mixed-methods blend of quantitative modeling and simple, descriptive online media analysis in the spirit of Robert Park's “Natural History of the Newspaper” is used to map the contours of competition, succession, and representation in a planetary urbanism that is now diagnosed as a new phase of “cognitive-cultural” capitalism. Cognitive-capitalist urbanism evolves along multiple semiotic frontiers of cosmopolitan diversity and multidimensional, intersectional hybridity – while valorizing performative competitive hierarchies that legitimate the reproduction of the structured inequalities of capital accumulation. Combinatoric expansion of the spatio-temporal reference points of identity and ancestry present daunting challenges to all who pursue equity or equality – requiring careful strategic confrontation of the meanings of neoliberal planetary human evolution.